Comparison of Wear Resistance of Hawley and Vacuum Formed Retainers: An in-vitro Study - Moshkelgosha V; Shomali M; Momeni M (Shiraz University of Medical Sciences, 2016)
Statement of Problem: As a physical property, wear resistance of the materials used in the fabrication of orthodontic retainers play a significant role in the stability and long term use of the appliances. Objectives: To evaluate the wear resistance of two commonly used materials for orthodontic retainers: Acropars OP, i.e. a polymethyl methacrylate based material, and 3A-GS060, i.e. a polyethylene based material. Materials and Methods: For each material, 30 orthodontic retainers were made according to the manufacturers' instructions and a 30×30×2 mm block was cut out from the mid- palatal area of each retainer. Each specimen underwent 1000 cycles of wear stimulation in a pin on disc machine. The depth of wear of each specimen was measured using a Nano Wizard II atomic force microscope in 3 random points of each specimen's wear trough. The average of these three measurements was calculated and considered as mean value wear depth of each specimen (µm). Results: The mean wear depth was 6.10µm and 2.15µm for 3A-GS060 and Acropars OP groups respectively. Independent t-test showed a significant difference between the two groups (p < 0.001). The results show Polymethyl methacrylate base (Acropars) is more wear resistance than the polyethylene based material (3A-GS060). Conclusions: As the higher wear resistance of the fabrication material can improve the retainers' survival time and its cost-effectiveness, VFRs should be avoided in situations that the appliance needs high wear resistance such as bite blocks opposing occlusal forces.